Penerapan Kebijakan Indonesia Sebagai Negara Anggota Organisasi CCSBT Commission for the Conservation of Southern Bluefin Tuna) Terhadap Pemberantasan IUU (Illegal Unreported and Unregulated) Fishing serta Penerapan Kuota Penangkapan - Selvi Dwi Septiarini; , I Wayan Nuarsa; Ni Luh Putu Ria Puspitha (Department of Marine Sciences, Faculty of Marine and Fisheries, Universitas Udayana, 2024)
Illegal, unreported, and unregulated fishing happens globally, especially in Indonesian waters; one of the problems that is often faced is compliance with fishing quotas. Furthermore, as a CCSBT member nation, Indonesia must adhere to all provisions put in place for the preservation of fish resources, particularly southern bluefin tuna. One of their requirements, following the provisions on the number of catches that apply to Indonesia, is to eradicate IUU fishing and fishing quotas; this study attempts to ascertain the measures made by Indonesia to enforce compliance with the CMM’s implementation for CCSBT. Interview method and an examination of relevant papers and regulations were used in this research tuna associations and government organizations involved in the management of bluefin tuna collected in 2021, Indonesia was 99% free from over quota according to the result of alleged IUU infractions committed by one of the tuna fishing vessels in the Indian Ocean RFMO area. Indonesia is required to pay back 91.3 tons per year over the following 5 years despite breaking the rules established by international bodies in 2019–2020. After the punishment, Indonesia is being more proactive in putting various initiatives into action to ensure the sustainability of southern bluefin tuna in the future.